On call : a doctor's journey in public service - Fauci, Anthony S., 1940- ([New York] : Viking, 2024)
"The memoir by the doctor who became a beacon of hope for millions through the COVID pandemic, and whose six-decade career in high-level public service put him in the room with seven presidents."--
Keywords: Fauci, Anthony S., -- 1940-; National Institute of Allergy and Infectious Diseases (U.S.) -- Officials and employees -- Biography; Government physicians -- United States -- Biography; Immunologists -- United States -- Biography; AIDS (Disease) -- Research -- United States -- Popular works; COVID-19 Pandemic, 2020- -- United States -- Personal narratives; COVID-19 Pandemic, 2020- -- Government policy -- United States -- Popular works; Autobiographies